Predictive Value of Intraoperative Troponin I Elevation in Pediatric Living Donor Liver Transplant Recipients With Biliary Atresia. Issue 10 (October 2017) - Sheng, Mingwei; Lin, Yuanbang; Weng, Yiqi; Xu, Rubin; Sun, Ying; Yu, Wenli; Du, Hongyin
Abstract : Background: Pediatric living donor liver transplantation is associated with slight alteration in cardiac enzymes without ongoing acute cardiac injury, but available information about the significance of these changes is limited. The aims of this study were to analyze the link between the anomalies of intraoperative serum cardiac troponin I (cTnI) and acute lung injury during the first week after liver transplantation. Methods: In this retrospective study, 123 children suffering from biliary atresia were enrolled. Several perioperative variables, particularly cTnI before operation and at 30 minutes of neohepatic phase were recorded. Sixty-four recipients were divided into high cTnI group (≥0.07 ng/mL) and 59 recipients composed normal cTnI group (<0.07 ng/mL). The clinical data between 2 groups were compared and the association between serum cTnI level and acute lung injury after living donor liver transplantation were evaluated by univariate and multivariate logistic regression analyses. Results: The percentage of acute lung injury after pediatric living donor liver transplantation among high cTnI group and normal cTnI group was 34.3% and 11.9%, respectively. Intratransplant cTnI ≥ 0.07 ng/mL (odds ratio [OR], 3.475; 95% confidence interval [CI], 1.114-10.842) was the risk factors for acute lung injury after transplantation. The value of cTnI showed the close correlation with preoperative bilirubin (OR, 1.005; 95% CI, 1.002-1.008) and pretransplant albumin (OR, 0.915; 95% CI, 0.849-0.986). Conclusions: Intraoperative cTnI elevation was the significant prognostic risk factor in acute lung injury after pediatric living-donor liver transplantation for children with biliary atresia. And the value of cTnI was associated with preoperative bilirubin and albumin level. Abstract : This group reports for the first time the elevation of Troponin in children receiving liver transplantation for biliary atresia with live donors and an association with pulmonary failure. Though the incidence of pulmonary failure is high in this cohort, the mechanistic possibilities of this observation are intriguing.